2006
DOI: 10.1074/jbc.m510032200
|View full text |Cite
|
Sign up to set email alerts
|

The Smaller Isoforms of Ankyrin 3 Bind to the p85 Subunit of Phosphatidylinositol 3′-Kinase and Enhance Platelet-derived Growth Factor Receptor Down-regulation

Abstract: The Src homology 2 (SH2) domains of the p85 subunit of phosphatidylinositol 3-kinase have been shown to bind to the tyrosinephosphorylated platelet-derived growth factor receptor (PDGFR). Previously, we have demonstrated that p85 SH2 domains can also bind to the serine/threonine kinase A-Raf via a unique phosphorylation-independent interaction. In this report, we describe a new phosphotyrosine-independent p85 SH2-binding protein, ankyrin 3 (Ank3). In general, ankyrins serve a structural role by binding to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…The up-regulated gene list also included several genes linked to signal transduction and gene transcription including GUCY1A3, an androgen-receptor-regulated guanylate cyclase implicated in prostate carcinogeneses (Dong et al, 2005), ANK3, a member of the ankyrin family of structural proteins (Ignatiuk et al, 2006) and STRA13, a basic helix-loop-helix (bHLH) transcription factor which regulates cell differentiation, proliferation, apoptosis and the response to hypoxic conditions (Ivanova et al, 2005). The up-regulated results also include chaperone genes.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated gene list also included several genes linked to signal transduction and gene transcription including GUCY1A3, an androgen-receptor-regulated guanylate cyclase implicated in prostate carcinogeneses (Dong et al, 2005), ANK3, a member of the ankyrin family of structural proteins (Ignatiuk et al, 2006) and STRA13, a basic helix-loop-helix (bHLH) transcription factor which regulates cell differentiation, proliferation, apoptosis and the response to hypoxic conditions (Ivanova et al, 2005). The up-regulated results also include chaperone genes.…”
Section: Discussionmentioning
confidence: 99%
“…As described below, several studies have suggested lower molecular weight isoforms of ankyrin G lacking most of the membrane binding domain localize to other subcellular compartments. For example, two studies demonstrated that the 100 kDa and 120 kDa isoforms present in mouse macrophages or expressed in 3T3 or COS-1 cells localize to late endosomes and lysosomes involved in protein degradation [72,73]. Furthermore, a 116 kDa (AnkG119) isoform present in kidney and muscle associates with the Golgi apparatus that packages proteins for secretion or transport within the cell [58].…”
Section: Reviewmentioning
confidence: 99%
“…For example, the small 110 and 120 kDa isoforms in late endosomes and lysosomes have been shown to contribute to lysosome-mediated downregulation of receptors by binding directly to the p85 subunit of phosphatidylinositol 3’-kinase (PI3K). This interaction modulates degradation of the platelet-derived growth factor receptor (PDGFR) that activates different downstream signaling cascades, including the PI3K-Akt and the Ras-MAPK pathways that mediate cellular processes including proliferation and survival [73]. Interestingly, the phosphoinositol pathway is a putative target of lithium and valproate [25,87-89], highlighting a potential overlap between the cellular functions of ANK3 with BD treatment response.…”
Section: Reviewmentioning
confidence: 99%
“…The movement of late endosomes to lysosomes can be experimentally inhibited by chloroquine (18,65). Therefore, the sensitivity of VRK1 downregulation to inhibitors of the transport system was tested by performing a dose-response analysis with chloroquine.…”
Section: Fig 3 Implication Of P53 Protein Domains In the Induction mentioning
confidence: 99%